Factors Causing Increasing Matters of Marriage (Case Study of Cikarang Religious Court) - Wicaksono, Fadillah Haryo; Ratnawaty, Latifah; Fajri, Ibrahim (Universitas Ibn Khaldun Bogor, 2025)
The itsbat marriage process is a formal request to validate a marriage, specifically for unregistered marriages that require legal recognition. Conducted in the Religious Court, itsbat marriage is pursued for various reasons and driven by multiple factors. This study explores the factors contributing to the rise in itsbat marriage cases in the Cikarang Religious Court from 2018 to 2024. A qualitative research approach was employed, combining empirical normative perspectives to connect relevant legal theories to the subject of this study. The research identifies two main questions: the reasons for the increase in itsbat marriage cases at the Cikarang Religious Court and the judges' considerations in relation to this increase. The study finds that the rise in itsbat marriage cases from 2018 to 2024 stems from internal factors, such as the need for official documentation, legal certainty for children’s status, and inheritance rights. External factors include a lack of public awareness regarding the importance of marriage registration with the Office of Religious Affairs (KUA) and previous administrative limitations that left marriages unregistered. Judges' considerations in itsbat marriage cases incorporate the principle of maslahah mursalah, prioritizing public benefit and justice to protect individual rights and provide legal clarity.